Understanding the psychological drivers of online self-presentation: a survey study on social media exposure, social comparison, social network type and FOMO - Thi Cam Tu Dinh; Yoonjae Lee (BMC Psychology)
Abstract Background Social media users can choose how to project their image to make a positive impression on others through social media. Although online self-presentation desire is an emerging phenomenon that engages with the users’ behavior on social media, empirical research and theoretical models on the topic are scarce. This study employs social comparison theory and the fear of missing out as mediators and social network type as a moderator to elucidate the effects of social media exposure on online self-presentation desire. Methods A quantitative survey was conducted among 367 social media users in the United States, recruited via Amazon Mechanical Turk. Partial least squares structural equation modelling (PLS-SEM) was used to test the hypothesised relationships among social media exposure, upward social comparison, FOMO, and online self-presentation desire, with social network type examined as a moderating variable. Results The findings indicate that frequent exposure to social media is more likely to result in upward social comparisons and experiencing fear of missing out, which motivates the users to self-present online. In addition, the difference between friend-dominated and stranger-dominated networks creates a powerful understanding of how they currently behave on social media platforms. Conclusions This study advances theoretical understanding by integrating social comparison theory and FOMO to explain how social media exposure drives online self-presentation desire, highlighting the moderating role of network type. The findings offer practical insights for users to manage their digital behavior and for businesses to tailor marketing strategies that align with users’ self-presentation motivations.